Engineering drawing and graphic technology - French, Thomas Ewing (McGraw-Hill, 1993)
The text is designed for students and teachers in high schools, community colleges, technical institutes, and first-year university level. The text is intended to provide a wide range of topics in the fundamentals of graphics. Full attention is given to modern treatment, up-to-date standards, and ease of organization. The material is organized so as to include more emphasis on newer aspects of the field, such as computer aided drafting (CAD) and a smoother integration of metric units.